Catalysis and tunnelling in the unimolecular decay of Criegee intermediates - Burd, T; Shan, X; Clary, D (Royal Society of Chemistry, 2018)
The unimolecular decay of Criegee intermediates is the major producer of OH radicals in the atmosphere. Here, Semi-Classical Transition State Theory (SCTST) in full and reduced dimensions is used to determine thermal rate constants for their unimolecular decay, as well as their decay catalysed by a single water molecule. These reactions shed light on the applicability of SCTST for catalysed hydrogen transfer reactions.